Social media and Internet-based communication in military families during separation: An international scoping review. (July 2023) - Wood, Abigail; Gray, Leanne; Bowser-Angermann, Joanne; Gibson, Poppy; Fossey, Matt; Godier-McBard, Lauren
The last decade has seen the growth of social media and Internet-based communication. Recent research highlighted the need for exploration of the use of social media by military families due to the significant period of separation that they experience. On this basis, an international scoping review was undertaken to explore how military families use Internet-based communication and social media to communicate with their serving members and what the impact of this is. The review showed a paucity of research focused specifically on the use of social media by Service families. Overall, papers returned showed that social media and Internet-based communication has distinct benefits for military families, fostering connectedness, increasing potential communication, enabling Serving parents to be more involved and better accommodate their family's routine, and potentially improving the deployment experience. However, unique practical barriers were also identified, alongside the potential exacerbation challenges associated with traditional forms of communication.